Perinatal Outcome in Preterm Caesarean Section at a Teaching Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Preterm caesarean section gives different perinatal outcomes.Objective: The purpose of the present study was to observe the different perinatal outcomes among the pregnant women with preterm caesarean section.Methodology: This prospective cohort study was conducted in the Department of Obstetric & Gynaecology at Shaheed Ziaur Rahman Medical College Hospital, Bogra, Bangladesh from January 2007 to December 2007 for a period of one year. Women with the gestational age between 32 to 36 completed weeks who were selected for delivery by caesarean section were selected as study population. Most of the pregnant women were brought to the hospital with poor condition. Actually the patients were managed on emergency basis. With the improvement of general condition of the patients, in consultation with anaesthetic department and paediatric department patients were managed accordingly and the perinatal outcomes were recorded.Result: A total number of 100 pregnant women were recruited for this study. In this study most of the pregnant women were in the age group of 15 to 25 years which was 60(60.0%) cases. Birth weight below 1.5 kg was in 15.0% cases. However, 72.0% babies had shown APGAR score within 4 to 7 at 5 minute. APGAR score more than 7 was present in 18.0% babies. In this study incidence of other diseases associated with prematurity was in 39(39.0%) cases and perinatal asphyxia was in 25(25.0%) cases. Among the women undergone preterm caesarean sections about 92(92.0%) cases were giving live birth and 8(8.0%) cases were reported still birth; however, subsequent neonatal death occurred in 27(27.0%) cases.Conclusion: In conclusion most common perinatal outcomes of preterm caesarean section is live birth with prematurity and perinatal asphyxia.Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 169-172